STATUS AND PROSPECTS FOR THE FIGHT AGAINST DIABETES MELLITUS - Abdurasul Taxirovich, Daminov; Nilufar Ulugbekovna, Rabbimova; Abduxalimova , Yulduz Jaxongirovna (Educational Research in Universal Sciences, 2024)
Diabetes mellitus remains one of the important medical and social health problems in almost all countries of the world. The prevalence of diabetes mellitus in industrialized countries is 5-6% and tends to increase. This is mainly due to the increase in patients suffering from non-insulin-dependent diabetes mellitus (NIDDM, type II diabetes). Thus, according to S. R. Kahn (1995), in the USA, about 6-7% of the general population are patients with NIDDM. Calculations have shown that if the average life expectancy increases to 80 years, the number of patients with NIDDM will exceed 17% of the total population[8-10]. The great social significance of diabetes mellitus is that it leads to early disability and mortality, which is caused by the presence of late vascular complications of diabetes: microangiopathy (retinopathy and nephropathy), macroangiopathy (myocardial infarction, stroke, gangrene of the lower extremities), neuropathy. Diabetes mellitus is a very common cause of blindness and death from uremia. People with diabetes are at greatest risk of developing cardiovascular disease. More than 40% of all non-traumatic lower extremity amputations are performed due to diabetic foot syndrome and gangrene of the lower extremities[1-7]. The main goals of the Diabetes Mellitus program are to radically increase the duration and improve the quality of life by providing specialized medical care to people with diabetes; carrying out the prevention of diabetes mellitus and its late complications using sufficient material and technical resources[11-14]. The program includes the following sections: 1) organization of diabetes service in the country; 2) organization of a system for the prevention of diabetes mellitus and its complications; 3) providing modern effective treatment for people with diabetes; 4) development of domestic production of medicines and diagnostics, food products for patients with diabetes[15-20].